A systematic review on role of humidity as an indoor thermal comfort parameter in humid climates. (1st June 2023) - Amaripadath, D.; Rahif, R.; Velickovic, M.; Attia, S.
Abstract: Thermal discomfort over time can lead to unproductivity and health issues for the occupants. Like operative temperature, humidity is an important parameter that affects thermal comfort and occupant health. This paper analyzed how humidity was incorporated into spatial and personalized thermal comfort assessments and models. In addition, the paper studied different indoor thermal comfort indices in terms of index type and time temporality. The study found that most standards and guidelines recommended a fixed upper and lower threshold for humidity for spatial assessment. For personalized assessments, the humidity was indirectly coupled through evaporative heat losses in most physiological and psychological models. In addition, transient processes like metabolic activities that changed in warm temperatures and humidities also influenced human comfort perception. The existing indoor thermal comfort indices used a point-in-time approach in terms of time temporality. Based on these findings, this paper suggested a spatial assessment for early-stage building design and a personalized assessment for the post-occupancy stage. In addition, this paper recommended a time-integrated and multizonal hygrothermal discomfort indicator that should incorporate both operative temperature and relative humidity in the future. Finally, the paper provides a set of suggestions and aspirations for practice and research based on the study findings. Highlights: Investigated role of humidity in indoor thermal comfort in humid climates. Qualitative two-pronged review considering spatial and personalized thermal comfort. The impacts of humidity cannot be overlooked when considering indoor thermal comfort. At high humidities, occupant comfort is highly dependent on their actions. The study findings and recommendations are useful in humid climates.